The Usage of the Characteristic Features of English Metaphors (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article devoted to the usage of the characteristic features of metaphors in English. Metaphor (from Greek metaphora — transfer) — is a hidden comparison built on the similarity or contrast of phenomena, in which the words «as», «as if», «as if there were no, but are implied in meaning, but not grammatically. Comparison is often confused with metaphor, as these tropes are based on — similarities between objects and phenomena. A metaphor is a figure of speech that implicitly compares two unrelated things, typically by stating that one thing is another (e.g., “that chef is a magician”). Metaphors can be used to create vivid imagery, exaggerate a characteristic or action, or express a complex idea.